Lifelong Learning and the Pursuit of Happiness: Questioning the Agenda for Adult Education - Patricia A. Gouthro (Adult Education Research Conference, 2006)
This paper explores how lifelong learning is connected with the pursuit of happiness, arguing that competing beliefs around what constitutes "happiness" and the "good life" influence the agenda for adult education.
Keywords: lifelong learning / happiness